Cave fragmentation in a cave-to-mill context at the New Afton Mine part I: fragmentation and hang-up frequency prediction. Issue 2 (3rd April 2018) - Nadolski, S.; Munkhchuluun, M.; Klein, B.; Elmo, D.; Hart, Craig
Abstract: Block and panel caving methods are increasingly being proposed as an economical means for the excavation of ore deposits. The development of methods for predicting cave fragment size holds significant potential for reducing risk associated with cave mining projects. A fragmentation study was carried out for the New Afton B1 and B2 caves to generate fragmentation models that could be applied to future lifts. In part 1 of this paper, implications of fragmentation size for the mine are considered, whereas the effects on mill performance are addressed in part 2. Fragmentation measurements, from sieving and image-based methods, as well as historical logs of hang-up events are presented. Measurements showed that for the B1 and B2 caves, secondary fragmentation size, representing the size of material at drawpoints, is strongly related to faulting, height of draw and effects of the cave boundary.